Analisis komparatif penerimaan pajak dan retribusi daerah sebelum dan sesudah pemberlakuan Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan Pemerintah Pusat dan Pemerintah Daerah di Badan Pendapatan Daerah Kota Manado - Tamyn, Linda Ignatia; Warongan, Jessy D. L.; Korompis, Claudia W. M. (Yayasan Widyantara Nawasena Raharja, 2025)
This study analyzes the impact of Law No. 1 of 2022 concerning the Financial Relationship between the Central and Regional Governments (UU HKPD) on local tax and retribution revenues in Manado City. Using a descriptive qualitative method, data were collected through interviews with the Regional Revenue Agency (Bapenda) and secondary data from revenue realization reports for 2023–2024. The results show that local tax revenues increased from IDR 369.47 billion in 2023 to IDR 403.74 billion in 2024, mainly due to tariff adjustments and the consolidation of several tax types into the Specific Goods and Services Tax (PBJT). However, the impact of the motor vehicle tax surcharge and transfer fee will only be seen in 2025. Meanwhile, local retribution revenues remained relatively stable, at IDR 4.74 billion in 2023 and IDR 4.57 billion in 2024, as Bapenda only manages waste retribution. These findings indicate that the UU HKPD significantly reshaped local tax structures but had limited effects on retribution revenues. The study highlights the need to optimize collection policies and expand the revenue base to strengthen Manado City’s fiscal independence.